Efforts To Improve The Quality Of Madrasa Graduates Through Curriculum Management In Islamic Boarding School K.H. Ahmad Dahlan Sipirok - Bahdin Nur Tanjung; Faisal Rahman Dongoran; Elfrianto Elfrianto (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The implementation of curriculum management is a series of resource management activities in implementing curriculum for the quality improvement. The purpose of this study was to find out how the planning, implementation, and evaluation of curriculum in improving the quality of graduates in the pesantren KH. Ahmad Dahlan Sipirok. This study uses a qualitative method. The technique of collecting data is by interview, observation, and document review. In addition, data and information are analyzed by data reduction, data exposure, and conclusion drawing. The results of the study were (1) curriculum planning was established by the madrasa leadership, MGMP, and teachers through curriculum planning meetings by making madrasa / pesantren education calendars, calculating effective working days for each subject, compiling annual programs, compiling semester programs, and implementing lesson plans as the direction of achieving academic quality and non-academic graduates, (2) the implementation of curriculum programs included learning using the curriculum of Diknas and pesantren through face-to-face learning, practice in mosques, halls, laboratories, and learning activities so that there were guidelines and targets achievement of the quality of graduates, (3) the implementation of curriculum evaluation included classroom supervision activities, learning evaluation, both formative and summative, and curriculum evaluation meetings at the end of the academic year which showed the achievement of the target of improving the quality of graduates could be seen from the fulfillment of minimum completeness criteria high and graduation of santri.